Survival of the Human in the Flux of Language: (Transcript of a lecture given as part of the School of Materialist Research - Intensive Study Program) - Nikolchina, Miglena (Identities: Journal for Politics, Gender and Culture, 2023)
The lecture examines aspects of the political, intellectual, and artistic contexts which triggered Julia Kristeva’s lifelong theoretical exploration of the “psychic revolution of matter” and which led to the formation of some of Kristeva’s major concepts. Author(s): Miglena Nikolchina Title (English): Survival of the Human in the Flux of Language (Transcript of a lecture given as part of the School of Materialist Research - Intensive Study Program) Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 116-127 Page Count: 12 Citation (English): Miglena Nikolchina, "Survival of the Human in the Flux of Language (Transcript of a lecture given as part of the School of Materialist Research - Intensive Study Program),” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 116-127.